Rapid mapping and analysing rock mass discontinuities with 3D terrestrial laser scanning in the underground excavation - Chen, S.; Walske, Megan; Davies, Ian (Pergamon, 2018)
© 2018 Elsevier Ltd Whilst laser scanning techniques have been shown to facilitate rapid identification and analysis of rock mass characteristics, relatively little research has been conducted for 3D laser scanning in underground spaces. In the present study, a semi-automatic laser scanning method has been presented for non-contact discontinuity identification and rock mass characterisation in a Western Australian underground gold mine. The accuracy of the 3D laser scanning technique was compared with traditional window mapping with a strong correlation being noted. The average dip/dip direction discrepancy between the two methods was found to be 1.5°/16° and attributed to the ability of 3D laser scanning to collect significant quantities of data when compared to traditional methods. Potential sources of error, together with the influence of the scale effect, were discussed with an optimum scanning resolution of 7.5 mm at 5 m being noted to provide a combination of significantly reduced collection and processing time and high levels of accuracy. Overall, the present study demonstrated the potential of 3D laser scanning techniques to replace traditional methods with increased efficiency and accuracy in underground mines.